PERIOD ANALYSIS OF THE RR LYRAE STAR AE BOOTIS - Bezdenezhnyi, V. P. (Одеські астрономічні публікації, 2017)
The Fourier analysis performed for photoelectric Periston's (1972) observations of the RRC Lyrae variable AE Boo shows that the star may be multiperiodic with most significant frequencies f1H, JF, f2H, 3/2 f F, 5/4 f F and their linear combinations.